Inheritance of seed characteristics in soybean progenies from grain type x food type crosses - Araujo, L. C. A. [UNESP] (2019)
Focusing on the genetic traits, seed coat and hilum pigmentation, in soybeans destined for human consumption is necessary due to the relevance of these traits for product acceptability by the consumer market. We investigated the traits seed coat, hilum color and bleeding hilum, in F2: 3 populations originating from crosses between the soybean grain type ('BRSMG 810C' with yellow seed coat, black hilum, and gray pubescence; bleeding hilum and white flower) with food types ('BRSMG 790A' with yellow seed coat and hilum, brown pubescence, no bleeding hilum and purple flower; 'BRSMG 800A' with brown seed coat and hilum, brown pubescence, no bleeding hilum and purple flower).We evaluated 317 plants from cross A ('BRSMG 810C' x 'BRSMG 790A') and 357 plants from cross B ('BRSMG 810C' x 'BRSMG 800A'). The resulting progenies adjusted to the expected ratio, considering four genes (R/I/W/T) controlling the expression of seed coat and hilum pigmentation for both crosses. In cross B, genotypes ii prevented the expression of the W and T alleles in the seed coat pigmentation. The expression of the bleeding hilum phenotype varied and presented monogenic inheritance, with complete dominance for no bleeding hilum. The genes responsible for bleeding hilum are linked with the T_ genotype (brown pubescence). Thus, in these crosses,hybridization was an efficient means to obtain genetic variability. This will aid in the production of for food grade soybean cultivars.